The Role of Leadership in Managing Multicultural Teams. Polish Managers’ Point of View: Preliminary Research - Agnieszka Knap-Stefaniuk (Studia Paedagogica Ignatiana, 2020)
Today, in the globalized world of the 21st century, the issue of leadership is topical and particularly important, hence it is not surprising that it is extensively analyzed in numerous publications. The role and significance of leadership primarily result from the fact that it has a great impact on the achievements of teams and companies, relations between people, their motivation to work, their openness to changes and new challenges, and a vision of the future development of the company. The theoretical part of the article first explains the concept of leadership and its significance, and next describes multiculturalism as a challenge for contemporary leadership in the context of managing intercultural teams. The empirical part presents the methodology of the study and the results obtained, which are followed by conclusions and recommendations. The research described in the article (ten telephone interviews) was conducted with international companies among managers who work with culturally diverse teams. At this stage the research is preliminary, and the author intends to conduct an in-depth study among managers of multinational companies in Poland and Spain that will investigate the role of leadership in managing multicultural teams. The main aim of the article is to demonstrate the importance of leadership in managing multicultural teams. Considering this aim, the following research question was formulated: How do Polish managers employed in multinational companies define leadership and how do they perceive the role of leadership in managing multicultural teams?